Biomechanics of cross country skiing - Smith, G. (2002)
Endurance sports such as running and cross-country skiing share many characteristics which make them attractive for alternative season activities. The joy of running forest trails is matched by skiing through the woods on tracks that roll up and down adapting to terrain. Running such trails can be physiologically demanding but involves relatively simple technique. The subtle adjustments of stride length and frequency, of foot placement and arm motion are rather intuitive and come naturally to most runners. In contrast, skiing such wonderful changing terrain requires a variety of complex techniques smoothly linked together. Both running and cross-country skiing demand large metabolic capacities; race results are certainly determined in large part by competitor physiology. But in skiing, technique and equipment probably play a much greater role in affecting performance. This chapter will explore the mechanical side of skiing--looking to explain the subtleties of technique, characteristics which drive performance, interactions of equipment, technique, and economy of motion. To understand the mechanical side of skiing, it will be helpful to use the tools that engineers and physicists use for analysis of inanimate systems. Biomechanics applies engineering methods to analysis of human motion; we'll explore what biomechanics can explain about skiing technique and performance. Mechanics can be broadly divided into two approaches: "kinematics" deals with descriptions of motion using characteristics such as displacement, speed, and acceleration while "kinetics" deals with the causes of motion such as force, torque, and energy. To understand human motion it is often helpful to start with kinematics so that one can quantitatively "picture" movement patterns. But ultimately, kinetic characteristics are what drive motion and which must be determined to approach understanding of complex movement patterns like those of cross-country skiing.